A rare case of bilateral drain site abdominal hernia: a case report and review of literature - Sonker, Santosh K.; Kujur, Lizrose; Agrawal, Harsh M. (International Surgery Journal, 2020)
Use of abdominal drain is a tradition used since a long time. These is generally done to prevent or drain any post-operative intra-abdominal collection aiming to reduce morbidity and mortality and early recovery of patient. But drain has its own complication such as drain site infection, drain site hernia. We encountered a case of bilateral drain site hernia in a 55 year old female who was previously operated for perforation peritonitis. Both herniae were repaired successfully with onlay meshplasty. Drain placement has various complications like drain site infection, adhesion’s, intestinal erosion, bleeding, anastamotic rupture and drain site hernia. There is greater risk of hernia in patient with poor nutritional status, obesity, ascitis, severe abdominal infection or with persistent cough. It is better to avoid unnecessary placement of drain. If a drain is placed, its removal should be done as early as possible. It is better to close the defect after removal of drain.